MORPHOLOGICAL CHANGES IN RECTAL TISSUE AFTER CHEMICAL EXPOSURE (Scientific journal of the Fergana State University, 2025)
The article presents a study of histological changes in the rectal mucosa of guinea pigs after exposure to chemical stress caused by alcohol poisoning. A detailed analysis of microstructural disorders was carried out, including destructive changes in the epithelial layer, inflammatory infiltration of the lamina propria of the mucous membrane, and pronounced vascular disorders.